Gospodarka oparta na wiedzy (GOW) w polityce innowacyjnej samorządu województwa podkarpackiego - Pasterz, Teresa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2007)
W artykule zaprezentowano działania podejmowane przez samorząd województwa podkarpackiego, na rzecz budowania podkarpackiej gospodarki opartej na wiedzy. Autorka analizuje, na ile dokumenty strategiczne, stanowiące potencjalne źródło finansowania rozwoju GOW w województwie podkarpackim w perspektywie najbliższych siedmiu lat (Regionalny Program Operacyjny Województwa Podkarpackiego na lata 2007-2013, makroregionalny Program Operacyjny Rozwój Polski Wschodniej oraz horyzontalne Programy Operacyjne Kapitał Ludzki i Innowacyjna Gospodarka) stymulują rozwój nowoczesnej gospodarki w regionie podkarpackim.

In the article there were presented some actions taken by the selfgovernment of podkarpackie voivodeship directed at building an economy based on knowledge in Podkarpacie. The author analyses to what extend strategic documents that constitute potential source for financing development of KBE in podkarpackie voivodeship in the nearest seven years (Regional Operational Program of Podkarpackie Voivodeship for the years 2007-2013, macroregional Operational Program Development of East Poland and horizontal Operational Programs Human Capital and Innovative Economy) stimulate development of a modern economy in Podkarpacie region.
Knowledge-Based Economy (KBE) in Innovation Policy of Self-Government of Podkarpackie Voivodeship